When are we operating for chronic rhinosinusitis? A systematic review of maximal medical therapy protocols prior to endoscopic sinus surgery. Issue 12 (22nd July 2015) - Dautremont, Jon F.; Rudmik, Luke
Abstract : Background: Endoscopic sinus surgery (ESS) is considered a therapeutic option after failure of maximal medical therapy (MMT) for chronic rhinosinusitis (CRS). There is currently no consensus on the definition of MMT. The objective of this systematic review is to describe the various MMT criteria employed prior to considering ESS. Methods: A systematic review was performed using the 2009 Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Inclusion criteria were adults with CRS based on guideline diagnostic criteria, enrolled to undergo ESS, and study publication within the last 5 years (January 1, 2009, to December 30, 2014). Studies were excluded if the study population included non‐CRS indications for ESS. Primary outcome was the MMT criteria employed prior to considering a patient a candidate for ESS. A subgroup analysis was performed based on polyp status. Results: Of 387 reviewed studies, 21% reported MMT criteria. When reported, criteria included topical nasal corticosteroids (91% of studies) for a mean of 8 ± 8 weeks, oral antibiotics (89%) for 23 ± 8 days, systemic corticosteroids (61%) for 18 ± 12 days, saline irrigations (39%), oral antihistamines (11%), oral mucolytics (10%), and topical/oral decongestants (10%). Conclusion: A minority of studies report MMT criteria used as the indication for ESS. When reported, the majority included an 8‐week course of topical intranasal corticosteroids and 3‐week course of oral antibiotics. Use of systemic corticosteroids did not differ based on polyp status. Because of variation in current MMT criteria, there is a need to develop standardized indications for ESS that will work to improve the appropriateness of care for patients with